Resilience, Trauma, Context, and Culture. (July 2013) - Ungar, Michael
This article reviews the relationship between factors associated with resilience, and aspects of the individual's social ecology (environment) that promote and protect against the negative impact of exposure to traumatic events. It is shown that the Environment × Individual interactions related to resilience can be understood using three principles: (1) Resilience is not as much an individual construct as it is a quality of the environment and its capacity to facilitate growth (nurture trumps nature); (2) resilience looks both the same and different within and between populations, with the mechanisms that predict positive growth sensitive to individual, contextual, and cultural variation (differential impact); and (3) the impact that any single factor has on resilience differs by the amount of risk exposure, with the mechanisms that protect against the impact of trauma showing contextual and cultural specificity for particular individuals (cultural variation). A definition of resilience is provided that highlights the need for environments to facilitate the navigations and negotiations of individuals for the resources they need to cope with adversity. The relative nature of resilience is discussed, emphasizing that resilience can manifest as either prosocial behaviors or pathological adaptation depending on the quality of the environment.